Associação entre climatério e indicadores nutricionais de obesidade em mulheres não usuárias de terapia de reposição hormonal - Lacerda, Marília Santana Sousa de (2016)
At the beginning of climacteric women experience progressive weight gain and metabolic complications and evolve with changes in the distribution of body fat deposits. The aim of this study was to investigate the association between menopause and nutritional indicators of obesity, adjusted for age, lifestyle and resistênncia insulin in nonusers women hormone replacement therapy. We conducted an analytical cross-sectional study in the period from August to December 2015, with 103 women attending the Climacteric Clinic of the University Hospital of Federal University of Maranhão and Clinical Research Center. It was applied to hum questionnaire containing sociodemographic variables, lifestyle and climacteric stage. Were assessed the nutritional indicators: body mass index, waist circumference, waist height and abdominal sagittal diameter. In addition to the biochemical blood glucose and fasting insulin markers, HOMA-IR, total cholesterol and fractions. We used Poisson regression model with robust variance to verify the association between menopause and anthropometric indicators of obesity. In this study, women in the postmenopausal age group had between 50 and 65 years (p <0.001), with more than 10 years of education (62.1%), income below the minimum wage (50.5%) and up to 3 children (68.9%). As for lifestyle 49.5% were classified as sedentary and most reported not drinking alcohol (72.8%) and smoking (95.1%). Observed higher percentages of WHtR (82.2% vs. 63.8%; p = 0.039) and triglycerides (48.9% vs. 22.4%; p = 0.005) higher compared with women in pre- menopause. There was no statistically significant difference for BMI and WC. In the analysis of nutritional indicators of obesity with climacteric adjusted for age, HOMA, physical activity, alcohol consumption and smoking, menopause was associated only with the WHtR model (PR = 1.15; p = 0.011) and HOMA-IR, with models IMC, CC, WHtR and SAD (PR = 1.51; 1.20; 1.22; 1.30, respectively;. p <0.001 was concluded that all models analyzed were associated with HOMA-IR . Only the model of WHtR was associated with perimenopause, demonstrating that this indicator has identified increased adiposity in the abdomen in postmenopausal women.